Analysis of Code Switching in Dialogue of Indonesian Novel Permainan Maut by Lexie Xu - Yosi, Ni Putu Diana; Sadia, I Gede (Humanis; Vol 23 No 3 (2019)DO - 10.24843/JH.2019.v23.i03.p02, 2019)
This undergraduate thesis entitled “Analysis of Code Switching in Dialogue of Indonesian Novel Permainan Maut by Lexie Xu” has two aims which are; to analyze the types of code switching and the functions of code switching that is found in the novel. The data source that is used in this study is a novel entitled Permainan Maut by Lexie Xu. It was chosen as the data because there are many characters who come from different social background that makes them often to talk in various languages. This phenomenon could help to analyze on how code switching works in every dialogues.   The data was collected using documentation method and analyzed using theory from Wardhaugh (1986) in his book entitled An Introduction to Sociolinguistics to analyze the types of code switching and from Appel & Muysken (1987) in his book entitled Language Contact and Bilingualism to analyze the functions of code switching.  Furthermore, it is presented in informal method using words to explain the type and function of code switching used by the character in their dialogue. The result of this study explains that Situational Code Switching is more dominant to be used than Metaphorical code switching. Not all functions of code switching can be found in these dialogues. Only four out of six are used, they are : Referential Function, Metalinguistics Function, Phatic Function and Expressive Function.